RANCANG BANGUN SISTEM INFORMASI KEPEGAWAIAN (STUDI KASUS: UNIVERSITAS KUNINGAN) - Aji Permana (NUANSA INFORMATIKA, 2020)
Design of Personnel Information System (A Case Study at Kuningan University) is a means to manage and obtain employee data both Lecturers and Educational staffs at Kuningan University. Management of this application includes employee data, employee documents, periodic payments, in passing, attendance, service personnel questionnaire and so forth. This Personnel Information System provides the official website of the personnel department as a means of information for employees as well as a public means for obtaining job vacancy information. The results obtained in this Personnel Information System consist of employee data reports, periodic, in passing and other approval data that can be adjusted according to the type of report and the range taken.Keywords: Personnel Information System